ConBus: Uma Plataforma de Middleware de Integração de Sensores para o Desenvolvimento de Aplicações Móveis Sensíveis ao Contexto - SÁ, Marcio Pereira de (2010)
In spite of the great evolution and dissemination of mobile devices and embedded sensors, development of ubiquitous applications is still a complex task mainly due to the great diversity of context information and the abundance of sensor technologies. In this scenario, middleware systems are responsible mediating communication between contextaware applications and sensors. This responsibility envolves many services such as sensor communication protocols, asynchronous communication, context information reasoning. In spite of their importance for mobile context-aware applications, the development of middleware platforms for context provisioning is also a very complex task, specially in terms of sensor module integration to these platforms. This happens due to many factors, such as: i) huge complexity to develop sensor modules; ii) dificulties of reuse of sensor modules; and iii) sensor module life cycle management. This work proposes a context provisioning middleware architecture for mobile devices named ConBus (Context Bus) that implements development, reuse, deployment and dynamic activation strategies for sensor modules.